2014
DOI: 10.1021/jf5005034
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Sesquiterpenes and Rutinosides from Murraya koenigii (L.) Spreng

Abstract: Three new sesquiterpenes (1-3) and two new rutinosides (4 and 5) along with 17 known compounds (6-22) were isolated from the leaves of Murraya koenigii (L.) Spreng. The new compounds were elucidated as (3R,5S,6R)-3,5,6-trihydroxy-1,1,5-trimethylcyclohexyl-8-butyn-9-one (1), (8E,9R)-ethyl-7-(3S,5R,6S)-3,6-dihydroxy-1,1,5-trimethylcyclohexyl-9-hydroxybut-8-enoate (2), (3R)-3-O-β-D-glucoside-6'-D-apiose-β-ionone (3), 4-O-β-D-rutinosyl-3-methoxyphenyl-1-propanone (4), and 1-O-β-D-rutinosyl-2(R)-ethyl-1-pentanol (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Featuring structural diversities, desirable bioactivities and environmental compatibilities, natural products provide plenty of template molecules for the development of novel medicines and agrochemicals. [1][2][3] As a heterocyclic nucleus, quinazolin-4(3H)-one widely exists in many bioactive natural products of medicinal plants, such as febrifugine ( Figure 1A), vasicinone ( Figure 1B), luotonin A ( Figure 1C), tryptanthrin ( Figure 1D), and so on. [4] Appearing fine effects on antimalarial, [5] antifungal, [6] anti-obesity, [7] anticancer, [8] antibacterial, [9] anti-flammatory, [10] insecticidal [11] and vasorelaxant [12] activities, natural quinazolin-4(3H)-ones show important applications and development perspectives in searching for bioactive lead compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Featuring structural diversities, desirable bioactivities and environmental compatibilities, natural products provide plenty of template molecules for the development of novel medicines and agrochemicals. [1][2][3] As a heterocyclic nucleus, quinazolin-4(3H)-one widely exists in many bioactive natural products of medicinal plants, such as febrifugine ( Figure 1A), vasicinone ( Figure 1B), luotonin A ( Figure 1C), tryptanthrin ( Figure 1D), and so on. [4] Appearing fine effects on antimalarial, [5] antifungal, [6] anti-obesity, [7] anticancer, [8] antibacterial, [9] anti-flammatory, [10] insecticidal [11] and vasorelaxant [12] activities, natural quinazolin-4(3H)-ones show important applications and development perspectives in searching for bioactive lead compounds.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Appearing fine effects on antimalarial, [5] antifungal, [6] anti-obesity, [7] anticancer, [8] antibacterial, [9] anti-flammatory, [10] insecticidal [11] and vasorelaxant [12] activities, natural quinazolin-4(3H)-ones show important applications and development perspectives in searching for bioactive lead compounds. [13] Further investigations on the structural optimization of quinazolin-4(3H)-ones found that introducing Schiff base, [14] amide, [15] 1,2,4-triazole, [16,17] 1,2,4-triazolo [3,4-b] [1,3,4]thiadiazole [18] and 1,2,4-triazolo[1,5-a]pyrimidine [19] scaffolds at the N-3 position of quinazolin-4(3H)-one could greatly enhance and broaden their antimicrobial activities. Strikingly, Zhang et al verified the antifungal mechanism of 3-acylaminoquinazolinone derivatives as chitinase inhibitors, and found a carbonyl group at the N-3 position of quinazolin-4(3H)-one nucleus plays a key role in inhibiting chitinous biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned compounds have been recognized as components of different natural flavours. For example 3-hydroxy and 3-keto-α-ionone, 4-hydroxy- and 4-keto-β-ionone and hydroxy-β-damascone isomers have been identified in curry tree [3], eucalyptus honey [4], saffron [5], black tea [6] and tobacco [7,8] respectively, whereas 3-keto-theaspirane (also known under the trade name theaspirone) is the character impact compound of the black tea flavour [9].…”
Section: Introductionmentioning
confidence: 99%
“…The high-resolution electrospray ionization mass spectrometry (HR-ESI− MS) data were measured with an Agilent 1100 series LC/MSD ion trap mass spectrometer (Agilent Technologies, Santa Clara, CA, U.S.A.), and ESI−MS spectra were recorded on a LTQ Orbitrap XL spectrometer (Thermo Fisher Scientific, Waltham, MA, U.S.A.). 20 Preparative high-performance liquid chromatography (HPLC) was performed on a Shimadzu LC-6AD instrument with a SPD-20A detector and a YMC-Pack ODS-A column (250 × 20 mm, 5 μm, Shimadzu Corporation, Japan). The HPLC data were measured using Agilent 1200 series with a DIKMA (4.6 × 250 mm) analytical column packed with C18 (5 μm, Agilent Technologies, Santa Clara, CA, U.S.A.).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%